2022
DOI: 10.3390/jcm11154474
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Culprit of Neuropathic Skin Pain in Long COVID-19 Patients: A Case Series

Abstract: Cutaneous neurosensory symptoms have become increasingly reported findings in COVID-19; however, these virus-related manifestations are largely overlooked, and their pathology is poorly understood. Moreover, alterations of skin sensibility currently recognize no clear histopathology substrate. The purpose of this study was to provide pathology evidence of neurosensory skin system involvement in COVID-19 patients complaining of subjective neurological symptoms affecting the skin. Out of 142 patients, six long C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, in a recent study conducted by Grieco et al [114], the authors investigated cutaneous subjective neurologic symptoms (sNSs) in both subjects with acute COVID-19 and long COVID syndrome. Six long COVID patients suffering from cutaneous sNSs, evaluated through the Neuropathy Total Symptom Score-6 (NTSS-6) questionnaire, underwent a histopathological examination of cutaneous areas affected by paroxysmal diffuse burning and itching sensations.…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a recent study conducted by Grieco et al [114], the authors investigated cutaneous subjective neurologic symptoms (sNSs) in both subjects with acute COVID-19 and long COVID syndrome. Six long COVID patients suffering from cutaneous sNSs, evaluated through the Neuropathy Total Symptom Score-6 (NTSS-6) questionnaire, underwent a histopathological examination of cutaneous areas affected by paroxysmal diffuse burning and itching sensations.…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…In the above-mentioned study, histopathological analyses showed the hypertrophy of dermal nerve fibers resembling dermal hyperneury, a rare form of small nerve hypertrophy that affects sensory C fibers [115], and these findings could explain the dysesthesia experienced by the studied patients. In addition, electroneurography was also performed on two patients, revealing altered dermal A delta and C neuronal fibers, although it remains to be clarified whether this was due to the direct action of the virus on the terminal nerve fibers or other indirect mechanisms [114].…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…Although neuropathic pain can have central or peripheral etiologies, neuropathic pain persisting for 3 months after acute COVID-19 infection has been attributed to peripheral neuropathy [ 135 , 136 , 137 , 138 ]. Although both small and large fiber nerves are affected, recent evidence has shown that it is the small diameter, lightly myelinated or unmyelinated nerves that are most susceptible to damage [ 139 ]. The lack of myelination leaves axons subject to local stressors, including those produced by immune dysregulation.…”
Section: Symptoms Of Long Covidmentioning
confidence: 99%
“…It is a sensory C-fibre phenomena seen in chronic COVID neuropathic skin pain (Figure 2). 5 Impairment of the peripheral nervous system in COVID is extremely common as it hosts ACE-2 receptors.…”
Section: Telogen Effluvium In Sars-cov-2 Infection: Histological Aspectsmentioning
confidence: 99%